Effect of Entrepreneurship Orientation, Marketing Capability, Social Media Use on MSME Performance in Kelapa Gading - Luigi Susanto; Rodhiah Rodhiah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study was to examine the entrepreneurial orientation, marketing capability, use of social media have an influence on the performance of Micro, Small and Medium Enterprises (SMEs) in Kelapa Gading. Sampling was done by non-probability sampling method. Data collection technique was using Purposive Sampling. Data collected by means of distributing online questionnaires through the Google Form application with a sample size of 100 respondents. The data analysis technique used the SEM method, and the data was processed using SmartPLS software. The results showed that entrepreneurial orientation had a positive and insignificant effect on the performance of Micro, Small and Medium Enterprises (SMEs) in Kelapa Gading, marketing capability had a positive and significant effect on the performance of Micro, Small and Medium Enterprises (SMEs) in Kelapa Gading, the use of social media had a positive and significant effect. on the performance of Micro, Small and Medium Enterprises (SMEs) in Kelapa Gading.